Optimal growth and impatience : a phase diagram analysis - Fwu-Ranq Chang (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper we show that we can replace the assumption of constant discount rate in the onesector optimal growth model with the assumption of decreasing marginal impatience without losing major properties of the model. In particular, we show that the steady state exists, is unique, and has a saddle-point property. All we need is to assume that the discount function is strictly decreasing, strictly convex and has a uniformly bounded first-derivative.
Keywords: C62; C61; O41; 330; recursive utility; decreasing marginal impatience; saddle point; bounded slope assumption; Optimales Wachstum; Steady-State-Wachstum; Nutzenfunktion; Abzinsung; Theorie